Oxovanadium(IV) complex of 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene for oxidation of benzoin - Maurya, Mannar R.; Sikarwar, Sweta; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Vanadyl sulphate reacts with 2-(alpha-hydroxyethyl)benzimidazole covalently bonded to chloromethylated polystyrene (PS-Hhebmz) cross-linked with 5% divinyl benzene to give PS-[VO(hebmZ)(2)]. Characterisation of the catalyst was carried out by IR, electronic and EPR spectroscopic studies, thermogravimetry, scanning electron micrographs and elemental analyses. Catalytic potential of the complex was tested for the oxidation of benzoin using tert-butyl hydroperoxide (TBHP) as an oxidant in methanol where benzil, methylbenzoate, benzoic acid and dimethylacetal were obtained as products. Various parameters such as different solvents and concentration of the substrate as well as oxidant have been taken into consideration for the maximum oxidation of the benzoin. Under optimised reaction conditions, a maximum of 98.9% conversion of the benzoin was achieved after 6 h of reaction time where selectivity of the obtained reaction products varied in the order: methylbenzoate (48.5%) > benzil (19.5%) > dimethylacetal (17.1%) > benzoic acid (11.5%). Neat complex was also prepared to compare its catalytic property with polymer-anchored one. EPR spectra of neat and polymer anchored catalyst are characteristics of V(IV) complexes with typical axial pattern and possible square pyramidal geometry. The identical EPR spectral patterns of both freshly prepared and recovered anchored catalysts indicate that the complex is stable and the coordination environment is retained at the end of the catalytic reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2-(alpha-hydroxyethyl)benzimidazole; oxidation of benzoin; polymer-anchored complex; Polystyrene; vanadium(IV) complex